Nurturing Leadership Among Underprivileged Youth:: A Program For Self-Formation For The Least, The Last, And The Lost (The Macau Ricci Institute Journal, 2020)
IntroductionAccording to Kolvenbach (1986), the purposes of Jesuit Education are embedded in three characteristics.•To promote dialogue between faith and culture.•To include a religious dimension that permeates the entire education.•To assist in the total formation of each individual within the human community.In the same vein, Jesuit higher education aims to nurture its students in whole-person development, hoping that students can change the world to be a better place for domicile (AJCU, 2020). For instance, the aim of higher education at one of the famous Asian Jesuit universities, Sogang University, is to teach individuals the essence of life vocation and the adoration of the Mighty God (Kim, 2008). Sogang University advocates humanity, whole-person development, and truth (Sogang University, 2020).  Similarly, Sophia University, a prestigious private Jesuit university in Japan, also champions whole-person development, the values of Catholicism, and truth (Sophia University, 2020). In other words, both Sogang University and Sophia University treasure Jesuit traditions, Catholicism, and self-formation (Sogang University, 2020).